Evaluation of efficacy of intravenous magnesium sulphate versus dexamethasone for prevention of postoperative sore throat in patients undergoing lumbar spine surgery in prone position: a prospective randomized double blind placebo controlled study - Sheikh, Shahnaz Ahmad; Mir, Aabid Hussain; Yousuf, Abida; Naqash, Imtiaz Ahmad (International Journal of Advances in Medicine, 2019)
Background: Endotracheal intubation is associated with postoperative sore throat. The aim was to evaluate the efficacy of intravenous magnesium sulphate versus dexamethasone for prevention of postoperative sore throat in patients undergoing lumbar surgery in prone position. Methods: 150 patients of ASA physical status I and II in the age group of 18 to 70 years were divided into three groups of 50 each. group I (magnesium sulphate) received intravenous magnesium sulphate 30 mg. kg-1 in a total of 50 ml of normal saline for 10 minutes after intubation, group II (dexamethasone group) received intravenous dexamethasone 8 mg in 50 mL normal saline for 10 minutes after intubation and group III (placebo group) received 50 ml of normal saline for 10 minutes after intubation. The incidence and severity of postoperative sore throat and hoarseness was assessed by an anesthesiologist unaware of the group allocation, on arrival in the post anesthesia care unit at 0 h, and at 1 h, 6 h, 12 h, and 24 h thereafter. Results: Both incidence and severity of sore throat and incidence of hoarseness was more in placebo group than magnesium sulphate group and dexamethasone group and was statistically significant (p<0.05) and was comparable between magnesium sulphate and dexamethasone groups. Conclusions: Endotracheal intubation is associated with sore throat and hoarseness of voice. Magnesium sulphate and dexamethasone given intravenously reduce the incidence and severity of sore throat and hoarseness associated with endotracheal intubation.